Rethinking PE-HD Bottle Recycling—Impacts of Reducing Design Variety - Lorenz P. Bichler; Thomas Koch; Nina Krempl; Vasiliki-Maria Archodoulaki (Recycling)
As the severe environmental impacts of plastic pollution demand determined action, the European Union (EU) has included recycling at the core of its policies. Consequently, evolving jurisdiction now aims to achieve a recycling rate of 65% for non-PET plastic bottles by 2040. However, the widespread use of post-consumer high-density polyethylene (rPE-HD) recyclates in household chemical containers is still limited by PP contamination, poor mechanical properties, and low environmental stress cracking resistance (ESCR). Although previous studies have explored the improvement of regranulate properties through additives, few have examined whether reducing the variety of extrusion blow-moulded PE-HD packaging could offer similar benefits. Therefore, two sorted fractions of rPE-HD hollow bodies were processed into regranulates under industrial conditions, including hot washing, extrusion, and deodorisation. Subsequently, both materials underwent comprehensive characterisation regarding their composition and performance. The opaque material, which was sourced from milk bottles in the UK, exhibited greater homogeneity with minor impurities, leading to improved ductility and melt strain hardening at moderate strain rates compared to the mixed material stream, which contained approximately 2.5% PP contamination. However, both rPE-HD recyclates exhibited similar short-term creep behaviour, relatively low strain hardening moduli, and were almost devoid of inorganic particles. Considering the sum of the investigated properties, melt blending with suitable virgin material is likely one of the most effective options to maximise regranulate utilisation in hollow bodies, followed by recycling-oriented packaging design (e.g., for efficient sorting), and the employment of advanced sorting technology.